A Large-Scale Study of Surrogate Physicality and Gesturing on Human–Surrogate Interactions in a Public Space - Kim, Kangsoo; Nagendran, Arjun; Bailenson, Jeremy N.; Raij, Andrew; Bruder, Gerd; Lee, Myungho; Schubert, Ryan; Yan, Xin; Welch, Gregory F. (Frontiers in Robotics and AI, 2017)
Technological human surrogates, including robotic and virtual humans, have been popularly used in various scenarios including training, education, and entertainment. Prior research has investigated the effects of the surrogate’s physicality and gesturing in human perceptions and social influence of the surrogate. However, those studies have been carried out in research laboratories, where the participants were aware it was an experiment, and the participant demographics are typically relatively narrow—e.g., college students. In this paper, we describe and share results from a large-scale exploratory user study involving 7685 people in a public space, where they were unaware of the experimental nature of the setting, to investigate the effects of surrogate physicality and gesturing on their behavior during human–surrogate interactions. We evaluate human behaviors using several variables, such as proactivity and reactivity, and proximity. We have identified several interesting phenomena that could lead to hypotheses developed as part of future hypothesis-based studies. Based on the measurements of the variables, we believe people are more likely to be engaged in a human–surrogate interaction when the surrogate is physically present, but movements and gesturing with its body parts have not shown the expected benefits for the interaction engagement. Regarding the demographics of the people in the study, we found higher overall engagement for females than males, and higher reactivity for younger than older people. We discuss implications for practitioners aiming to design a technological surrogate that will directly interact with real humans.